1995
DOI: 10.1289/ehp.95103714
|View full text |Cite
|
Sign up to set email alerts
|

Do Waste Incinerators Induce Adverse Respiratory Effects? An Air Quality and Epidemiological Study of Six Communities

Abstract: The purpose of the study presented here was to simultaneously measure air quality and respiratory function and symptoms in populations living in the neighborhood of waste incinerators and to estimate the contribution of incinerator emissions to the particulate air mass in these neighborhoods. We studied the residents of three communities having, respectively, a biomedical and a municipal incinerator, and a liquid hazardous waste-burning industrial furnace. We compared results with three matched-comparison comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Details of the study design are presented elsewhere. 11 An overview of the study is shown in Figure 1.…”
Section: Study Design and Study Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the study design are presented elsewhere. 11 An overview of the study is shown in Figure 1.…”
Section: Study Design and Study Subjectsmentioning
confidence: 99%
“…11 The exposure could have been so low that it was unlikely to elicit any measurable effect on pulmonary function. However, the contribution of the incinerator to area fine mass was not estimated in the 3-or 12-month period preceding the annual spirometric tests, and contribution of other unmeasured pollutants from the emissions was not estimated.…”
Section: Communitymentioning
confidence: 99%
“…Studies on incinerators in France and in Italy have suggested an increased risk of non-Hodgkin lymphoma (NHL) [15], soft-tissue sarcoma [16,17], lung cancer [18], and neoplasia of the nervous system and liver [12]. Although the studies conducted by Shy et al [19] and Lee and Shy [20] did not show respiratory effects. Other studies have reported increases in respiratory diseases or symptoms in populations residing near incinerators [21,22,23,24] and in children [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The main lung effects investigated among workers are respiratory symptoms and pulmonary function [513]. In particular, the presence of functional respiratory alterations attributable to the current levels of exposure is controversial.…”
Section: Introductionmentioning
confidence: 99%